Molybdenum disilicide-silicon nitride bushing nozzles tailor-made for basalt fibers production. Issue 10 (1st August 2016) - Caretto, Flavio; Laera, Anna Maria; Di Nuzzo, Felice; Iovino, Rossella; Di Benedetto, Francesca; Pesce, Emanuela; Re, Marilena; Schwarz, Massimo; Tapfer, Leander
Abstract: A carefully comparative study of several ceramics compounds allowed the identification of MoSi2 blended with Si3 N4 as a suitable material for the realization of bushing nozzles, specifically designed for basalt fibers production. Degradation static tests were developed and performed to demonstrate the high resistance to oxidation at operating temperature of MoSi2 -Si3 N4 composites with respect to alumina, zirconia stabilized with magnesia or yttria, pure MoSi2, pure Si3 N4, and MoSi2 englobing SiC. Moreover, the MoSi2 -Si3 N4 composites resulted resistant to corrosion and chemical inert with respect to oxidizing components present in basalt melts. Bushings in MoSi2 -Si3 N4 were obtained by using hot isostatic pressing and were processed through mechanical drilling. The basalt fibers produced with the MoSi2 -Si3 N4 bushing showed a constant diameter and a regular surface morphology. The bushing was recovered intact without defects or fractures demonstrating the efficiency of the selected material. Replacing platinum-rhodium bushings with ceramic ones could greatly reduce costs of basaltic fibers production and could encourage the use of these eco-friendly, natural fibers as reinforcement in lightweight polymer composites.